ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP USAHA KECIL DAN MENENGAH CAR FREE DAY KABUPATEN PAMEKASAN - Nur Syakherul Habibi; Kasanova, Ria; Anisa Fajriana Oktasari; Fetty Nuritasari; Devie Reztia Anjarani (Journal of Innovation Research and Knowledge, 2022)
Car Free Day Small and Medium Enterprises are required to continue to strive to improve services to satisfy consumers and increase competitiveness. This study aims to analyze the level of consumer satisfaction with Car Free Day Pamekasan SMEs based on reliability, responsiveness, assurance, empathy and physical form. This research is a case study, the research subject is a consumer of UKM Car Free Day Pamekasan, during the month of February-March 2022. The number of samples is 100 people using the purposive sampling method. Data collection techniques using questionnaires and literature study. While the data processing technique uses analysis of the Customer Satisfaction Index (IKP), both overall and per attribute. The results of the study show: (1) the characteristics of the Car Free Day SME consumers are mostly female, aged between 29-39 years, the last education is D3/S1/S2/S3, employment status is private employee, with monthly income between Rp.2,000 .000,- up to Rp.3,000,000,-) and more than 5 times transactions at UKM Car Free Day Pamekasan. (2) In general, consumers are satisfied with the service of UKM Car Free Day Pamekasan. The results of data analysis show that 74% of respondents are very satisfied, 8% of respondents are satisfied, and 18% of respondents are dissatisfied, and (3) of the five attributes measured, in general on each attribute consumers feel very satisfied or at least satisfied, those who are not satisfied are not. more than 25%. The attributes that give the most satisfaction are the attributes of responsiveness, followed by attributes of physical form, reliability, assurance, and empathy